2013
DOI: 10.1002/asi.22786
|View full text |Cite
|
Sign up to set email alerts
|

Seeking information for a middle school history project: The concept of implicit knowledge in the students' transition from Kuhlthau's Stage 3 to Stage 4

Abstract: The article reports the findings of a content analysis study of 16 student-group proposals for a grade eight history project. The students listed their topic and thesis in the proposal, and information in support of their thesis. The study's focus is this topic-to-thesis transition. The study's conceptual framework is Kuhlthau's six stage ISP Model's transition from exploring information in Stage 3 to formulating a focus or personal perspective on the assignment topic in Stage 4. Our study coding scheme identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 42 publications
0
13
0
2
Order By: Relevance
“…This making sense is a “cumulative and developmental process” (Todd, ), the end result of which is students' construction of their own “world views” on the project topic (Kuhlthau et al., , p. 32). This construction of a personal world view or perspective on the project topic implicates the “whole person in thinking, acting, reflecting, discovering ideas, making connections, and transforming prior knowledge, skills, attitudes, and values into new knowledge” (Todd, ; see also Cole et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…This making sense is a “cumulative and developmental process” (Todd, ), the end result of which is students' construction of their own “world views” on the project topic (Kuhlthau et al., , p. 32). This construction of a personal world view or perspective on the project topic implicates the “whole person in thinking, acting, reflecting, discovering ideas, making connections, and transforming prior knowledge, skills, attitudes, and values into new knowledge” (Todd, ; see also Cole et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Related to this, Cole et al. () found that middle students' implicit knowledge identified in their proposal, which is assigned in the transition period between the exploration stage to the focus formulation stage of the ISP model, can be a predictor of successful student performance.…”
Section: Literature Reviewmentioning
confidence: 94%
“…The ISP has been frequently used as a framework in many information behavior studies in learning and research contexts at the elementary school through graduate and faculty levels (e.g., Bilal, ; Chu, Tse, Loh, & Chow, ; Cole et al., ; Harada, ; Holliday & Li, ; Hyldegård, ; Jiao, Onwuegbuzie, & Bostick, ; Pennanen & Vakkari, ; Serola & Vakkari, ; Todd, ) as well as in occupational contexts (e.g., Byström, ; Byström & Hansen, ; Kuhlthau & Tama, ; Vakkari, ). However, only a few studies have applied it to the information‐seeking behaviour of ELL students.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The researcher will conduct a content analysis on the students' projects and generate scores to be compared to those of previous cohorts and also to the grades assigned by the teachers (Cole et al ., 2013). Furthermore face‐to‐face individual interviews with students will provide the researcher with valuable qualitative data about the students' use of KAs and the transfer of experiential knowledge from previous student cohorts to new students.…”
Section: Methodsmentioning
confidence: 99%
“…The preliminary results of an ongoing study of successive cohorts of grade eight students working on an inquiry based history project show that students generate knowledge (Cole et al ., 2013). As the same history project is assigned to students of each new cohort, the researcher asks the following question: can the transfer of experiential knowledge from previous student to new students' working on a similar project improve their research process and their results?…”
Section: Introductionmentioning
confidence: 99%